2000
DOI: 10.1002/1529-0131(200008)43:8<1710::aid-anr6>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage degradation and invasion by rheumatoid synovial fibroblasts is inhibited by gene transfer of a cell surface-targeted plasmin inhibitor

Abstract: Objective. Joint destruction in rheumatoid arthritis (RA) is a result of degradation and invasion of the articular cartilage by the pannus tissue. The present study was undertaken to examine the role of the plasminogen activation system in cartilage degradation and invasion by synovial fibroblasts and investigate a novel gene therapeutic approach using a cell surface-targeted plasmin inhibitor (ATF.BPTI).Methods. Adenoviral vectors were used for gene transfer. The effects of ATF.BPTI gene transfer on RA synovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2001
2001
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 26 publications
0
27
0
2
Order By: Relevance
“…Although it is still too early to know whether distinct serine proteinase cascade(s) occur in RA and OA, it is evident that there is overlap in terms of collagenolysis (148,176,183). Further understanding of the complex roles of these enzymes, their substrate specificities, and identification of novel serine proteinases in the arthritic joint will provide new opportunities to identify tractable therapeutic targets that effectively prevent pathologic tissue turnover in RA and OA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is still too early to know whether distinct serine proteinase cascade(s) occur in RA and OA, it is evident that there is overlap in terms of collagenolysis (148,176,183). Further understanding of the complex roles of these enzymes, their substrate specificities, and identification of novel serine proteinases in the arthritic joint will provide new opportunities to identify tractable therapeutic targets that effectively prevent pathologic tissue turnover in RA and OA.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been established that plasmin can activate procollagenases (36), leading to the suggestion that the PA/plasmin cascade might function in various resorbing tissues to activate proMMPs, including procollagenases (37). A role for this cascade in the activation of endogenous cartilage metalloproteinases was subsequently reported (181,182), and there is also evidence for its presence in invasive rheumatoid synovium (183).…”
Section: Serine Proteinases and Activation Of Procollagenases In Cartmentioning
confidence: 99%
“…2,18 Neovascularization inhibition in experimental arthritis models has been previously evaluated using various inhibitors, such as tranexamic acid inhibiting plasmin, 19 the cell surface-targeted plasmin inhibitor ATF-BPTI, 20 cyclopeptides antagonist of integrin ␣V␤3, 6 a fumagillin derivative AGM-1470 toxic to proliferative endothelial cells, 7,19 or a monoclonal antibody inhibiting VEGF. 9 All these data demonstrated the efficiency of antiangiogenic strategies in RA.…”
Section: Discussionmentioning
confidence: 99%
“…23 Our data showed that mATF-HSA-sustained expression inhibited synovial angiogenesis at the early phase of arthritis since the number of vessels observed in the inflamed paws was significantly decreased in Ad-mATF-HSA-treated animals. Van der Land et al 20 have recently evaluated a similar construct containing ATF gene in a SCID/hu model, where the human synovial cells are isolated and cultured in an inert sponge before implantation in the kidney capsule. They clearly demonstrated a decreased synovial cell invasion and cartilage matrix degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Although all classes of proteolytic enzymes seem to be involved, it is generally believed that matrix metalloproteinases (MMPs) are pivotal in cartilage destruction. 3,4 MMPs are a family of zinc-dependent proteolytic enzymes that have the ability to degrade almost all proteins of the extracellular matrix. MMPs are divided into subgroups including: collagenases (MMP-1, -8, -13), gelatinases (MMP-2, -9), stromelysins (MMP-3, -7, -10, -11, -12), and membrane-type (MT) MMPs (MT1-MMP, MT2-MMP, MT3-MMP, MT4-MMP also termed MMP-14, -15, -16, and -17).…”
Section: Introductionmentioning
confidence: 99%